Comparison of Amount of Salivary Total Antioxidant in Patients with Recurrent Aphtous Stomatitis - Asma Madhani; Samira Shah Siah; Arash Azizi (Tehran University of Medical Sciences, 2012)
Background and Aims: Recurrent aphthous stomatitis (RAS) is the most common oral mucosal inflammatory disease. The frequency of RAS is as much as 20% in the general population. The cause of RAS is not yet fully understood. Antioxidant is a material which has ability to preserve molecules from damage and also can delay the start of it. The aim of this study was to compare saliva level of total antioxidant status (TAS) in RAS patients with that of normal subjects.Materials and Methods: In this case-control study, 25 patients with aphthous stomatitis were considered as the case group and 25 healthy subjects as control group. The case and control groups were matched by sex and age. Total antioxidant status (TAS) saliva levels were measured in two groups by spectrophotometer. The data were analyzed with independent sample t-test.Results: The mean and standard deviation of TAS in case group was 1.64±0.64 µmol/L and in control group was 1.49±0.3 µmol/L. There was not significant difference between case and control groups (P=0.464).Conclusion: Results of this study showed that there was no statistically significant difference between RAS patients and healthy subjects in saliva antioxidant status levels.